(untitled) (Damu Journal of Sport Sciences, 2025)
Studying the history and development of sports and understanding their achievements is of great importance, as they are considered a means of advancing societies. Sports are also a measure of a nation's cultural level. University sports are of great importance in providing teams and national teams with a wealth of youthful potential. Numerous tournaments are held at the university level for all sports, in which university students participate to compete with each other in a spirit of high culture, with the goal of entertaining students. Volleyball is a long-standing sport in Iraq, particularly among university students. In this research, the researcher explored the results of the University of Baghdad team through its participation in Iraqi university championships (for students) and archived data for the period from 1999 to 2024. He also analyzed, analyzed, and discussed these participations. The nature of the research required the researcher to use the historical method, or what is known as the documentary method, drawing on the historical development of these participations in university championships. As for the methods of collecting information, the researcher relied on written sources (books and magazines) and the World Wide Web (the Internet). He also relied on personal interviews with pioneers of the game in Iraq (such as the university team coach and player). The most important results reached by the researcher are that many of the participations of the University of Baghdad student volleyball team in university championships are not documented, and therefore several advanced positions were achieved without documenting them. As for the recommendations, the researcher recommended the need to pay attention to documenting university championships on a regular basis, as well as creating a special registry for them and recording the names of the players participating in these championships.